339 Life-time cumulative lift load and lumbar disc degeneration. (11th October 2013) - Guo, L; Hung; Shih; Chen; Hwang
Abstract : Objectives: Lumbar disc degeneration (LDD) has been associated with cumulative lift load. However, dose-response relationship has not been established in Asia workers. The goal of this study is to investigate whether a dose-response relationship exists between LDD and lifetime cumulative lift load on lumbar disc. Methods: A total of 553 subjects who have ever worked were recruited. The participants received assessment with a questionnaire and magnetic resonance imaging (MRI) of the L-S spine. The compression force on lumbar disc was estimated by using the 3-Dimension Static Strength Prediction Program (3D-SSPP, Center for Ergonomics, University of Michigan) software system. For each job described, the load on lumbar disc was calculated as the product of the compression force and the duration of lifting in hours. The lifetime cumulative load (Newton*hours, Nh) for each participant was then estimated by summing up the load on lumbar disc for all jobs. Logistic regression was used to assess association between MRI abnormalities and lifetime cumulative lifting load. Results: The subjects were categorised into tertiles by lumbar cumulative lift load, i.e., <4.0 × 10 5, 4.0 × 10 5 <8.9 × 10 6, and > = 8.9 × 10 6 Nh. The prevalence rates of LDD findings varied by disc level. Observed LDD findings increased with cumulative lift load. At the L5-S1 disc level, MRI findings of disc height narrowing (Odds ratio, OR = 4.1, 95% Confidence interval, CI 1.9 10.1), dehydrationin (OR = 2.5, CI 1.5 4.1), disc protrusion (OR = 2.2, CI 1.2 4.1), annulus tear (OR = 2.2, CI 1.2 4.2), disc bulging (OR = 1.9, CI 1.2 3.1) was found among those with cumulative lifting load of > = 8.9 × 10 6 Nh as compared to those with <4.0 × 10 5 Newton-hours. The tests for trend were significant (p < 0.05) for all above-mentioned disc conditions. Conclusions: Our results suggest a dose-response relationship between cumulative lift load and LDD.